2020
DOI: 10.1002/jcop.22471
|View full text |Cite
|
Sign up to set email alerts
|

Best friends, bad food, and bullying: How students’ school perceptions relate to sense of school belonging

Abstract: A positive school climate and sense of school belonging can influence students' academic outcomes and wellbeing in desirable ways. However, not enough is known about the aspects of school climate that influence students' feelings of belonging and how gender, ethnicity, and grade may relate to those feelings. Via a self-administered survey, a diverse sample of middle school students (n = 1,226) reported what they perceived as the best parts of their school and the parts most in need of improvement, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…A previous cross-sectional study in Scotland found that an inclusive school climate was significantly and positively associated with higher school belonging (Long et al, 2021). A U.S. study of middle school students also found that four dimensions of students' perceived school climate-safety, relationships, teaching and learning, and school environment-predicted varying degrees of school belonging (Renick and Reich, 2021). These studies support our finding of an association between a negative school climate and school belonging.…”
Section: Discussionsupporting
confidence: 88%
“…A previous cross-sectional study in Scotland found that an inclusive school climate was significantly and positively associated with higher school belonging (Long et al, 2021). A U.S. study of middle school students also found that four dimensions of students' perceived school climate-safety, relationships, teaching and learning, and school environment-predicted varying degrees of school belonging (Renick and Reich, 2021). These studies support our finding of an association between a negative school climate and school belonging.…”
Section: Discussionsupporting
confidence: 88%
“…For example, findings on gender differences regarding the sense of school belonging are quite inconsistent, and some research results indicate that the sense of school belonging is more pronounced in female students (Allen & Kern, 2017;Nuttman-Shwartz, 2019). Others present findings in favour of male students (CESE, 2020;Renick & Reich, 2020), or find that differences do not exist (Cemalcilar, 2010). Although the age of students has not been particularly examined in the context of significant factors, there is evidence that the sense of school belonging decreases linearly with age, so that high school students report the lowest level (Anderman, 2003;Renick & Reich, 2020).…”
Section: Individual Factors Of the Development Of The Students' Sense...mentioning
confidence: 99%
“…The main source of individuals’ maladaptive cognition is the irrational cognition toward themselves and the irrational cognition toward the world ( Mai et al, 2012 ). Previous studies show that a good social support system would contribute to the formation of individuals’ positive cognition such as a sense of belonging and wellbeing ( Borkar, 2016 ; Gabriella et al, 2020 ; Renick and Reich, 2020 ; Zhou, 2020 ). On the contrary, individuals with childhood trauma and social exclusion are more likely to hold negative cognition and emotional experience toward the world and themselves ( Choi et al, 2020 ; Angelakis and Gooding, 2022 ), which promotes individuals to explore a new path to escape from the old environment, where they can establish their new identity and satisfy themselves.…”
Section: Related Background and Hypothesismentioning
confidence: 99%